Restraint training for awake functional brain scanning of rodents can cause long-lasting changes in pain and stress responses. Issue 8 (August 2016) - Low, Lucie A.; Bauer, Lucy C.; Pitcher, Mark H.; Bushnell, M. Catherine
Abstract : Abstract: With the increased interest in longitudinal brain imaging of awake rodents, it is important to understand both the short-term and long-term effects of restraint on sensory and emotional processing in the brain. To understand the effects of repeated restraint on pain behaviors and stress responses, we modeled a restraint protocol similar to those used to habituate rodents for magnetic resonance imaging scanning, and studied sensory sensitivity and stress hormone responses over 5 days. To uncover lasting effects of training, we also looked at responses to the formalin pain test 2 weeks later. We found that while restraint causes acute increases in the stress hormone corticosterone, it can also cause lasting reductions in nociceptive behavior in the formalin test, coupled with heightened corticosterone levels and increased activation of the "nociceptive" central nucleus of the amygdala, as seen by Fos protein expression. These results suggest that short-term repeated restraint, similar to that used to habituate rats for awake functional brain scanning, could potentially cause long-lasting changes in physiological and brain responses to pain stimuli that are stress-related, and therefore could potentially confound the functional activation patterns seen in awake rodents in response to pain stimuli. Abstract : Restraint training caused long-lasting reductions in pain behavior, in response to the formalin test, and increases in amygdala cell activation.